(untitled) (Transport systems and technologies, 2024)
One of the peculiarities for switch operation is the increased level of force interaction between the bearing elements of the switch and the rolling stock chassis, which causes increased requirements for strength, stability, reliability and durability of switches. Accordingly, to assess the strength of structures, it is necessary to know the magnitude of the forces acting on them, which can be determined experimentally or by theoretical calculations. In the case of tunnel sections of subways, experimental studies are extremely difficult to organize and conduct, so only theoretical methods are an alternative. This study presents the results of theoretical calculations of the elastic-dynamic characteristics for railway switches used in tunnel sections of subways. Practical calculations of the stiffness of rail threads and the modulus of elasticity of the sub-rail base were performed, and dependencies of the distribution of elastic-dynamic parameters along the length of railway switches were obtained. On their basis, the forces of interaction with the subway rolling stock were determined and their distribution along the length of the railway switch was analyzed. The obtained data can serve as a prerequisite for checking the strength of structural elements.